BACTERIAL DESULPHURIZATION OF COALS - І. А. Блайда; Т. В. Васильєва (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2017)
The review contains literature data about the amount of various forms of sulfur in coals and its impact on the qualitative characteristics of coal. The technological and environmental problems resulting from the combustion of high-sulfur coals are shown. The problems of coal enrichment are considered and an overview of modern methods for their desulfurization are presented. Particular attention is paid to the biotechnological methods with using microorganisms of various taxonomic groups. Data about the reduction of sulphur content in the coals, mainly pyrite, under the action by representatives of mesophilic and moderately thermophilic acidophilic chemolithotrophic bacteria are given. A comparative analysis of the ability of the bacteria of the genera Pseudomonas, Bacillus, Brevibarterium and others to destroy the sulfur-containing heteroatom included in the structural matrix of coal are else given. The data on the role of heterotrophic bacteria in the oxidation of organic sulfur are shown.